Towards a theory of sustainable city sizes - Liton Md Kamruzzaman (npj Urban Sustainability)
Abstract This study proposes a new theory of sustainable city size: the condition where a city’s actual population aligns with its theoretical capacity to function effectively. Drawing from four foundational theories (locational fundamentals, increasing returns, central place, and central flow), the study develops a conceptual framework to estimate theoretical city size using data from 655 Urban Centres and Localities (UCLs) in Australia. It examines how deviations of actual size from this theoretical size influence sustainability outcomes, using rent, walking-to-work rates, and multi-vehicle household share as proxies for economic, environmental, and socio-environmental sustainability. Results show that UCLs within ±4% of their theoretical size achieve optimal outcomes across all indicators. Nationally, achieving equilibrium could save $5.3 billion in annual rent, generate 44,000 additional daily walking trips, and reduce multi-vehicle dependency in 275,000 households. These findings support the proposed theory and offer a practical tool to align cities with their systemic capacity.